INCREASING EXPORT COMPETITIVENESS THROUGH IMPROVING TRADE FACILITIES AND TRANSPORTATION INFRASTRUCTURE - Ansofino, Ansofino; Momon, Momon; UH, Vivi; Aldjoeffry, Mohammad Fikrie (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2024)
The main objective of this research is to analyze the economic agglomeration pattern of competitiveness of the main export products of West Sumatra province, focusing on the role of improving trade facilities and transportation infrastructure to and from the export port. How strong is its competitiveness, able to interact to serve national, regional and global trade, what strategies will be adopted to increase export competitiveness? The approach to measuring agglomeration export competitiveness used the Lapay Index, Moran and LISA Index, as well as factors influencing the creation of agglomeration using the spatial lag model and spatial error model, as well as strategies for increasing export competitiveness using the Promethee model. The research results show that aspects of existing transportation infrastructure and trade facilities have placed the competitiveness of West Sumatra province lower at the national and regional levels. Export ports have not interacted heavily with national and regional export port nodes. Strategy to increase the agglomeration of West Sumatra's export competitiveness through increasing ship units loading and unloading at export ports, increasing the number of containers (teus), increasing warehousing, improving the regulatory environment and increasing ICT capabilities at export ports.